Evaluasi Usability Sistem Manajemen Laporan Pemancar RRI Manado Berbasis Web Menggunakan Metode System Usability Scale - Melyssa Christy Pasiowan; Janari Jayanti Angela Kuru; Evert Paul Mangimbelat; Franky Gerald Cliford Manoppo; Maya Ernie Inneke Munaiseche (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Manual management of radio transmitter technical reports leads to recording errors, unstructured data, and inefficient report retrieval. This study aims to develop a web-based transmitter report management system and evaluate its usability using the System Usability Scale (SUS) method. The system was designed following the Waterfall development methodology and supports five types of report forms—Program 1, Program 2, Program 3, Program 4, and Stabilizer—each with distinct field structures and technical parameters. Testing was conducted at RRI Manado, involving five transmitter technician respondents who completed task scenarios based on real operational activities, including report creation, report editing, draft saving, and exporting reports to PDF. Evaluation data were collected using the SUS questionnaire, which consists of ten Likert-scale statements, and were analyzed using the standard SUS formula and interpreted with the adjective rating scale. The evaluation results showed an average SUS score of 81 points, which falls into the Good category and is considered Acceptable. Additionally, time efficiency measurements indicated that the system was able to reduce the average report completion time by 93.7% compared to the manual method. Despite differences in report formats, the system’s interface and workflow remain consistent, eliminating the need for users to learn a different process for each report type. This system can be used as a digital solution for transmitter report management at RRI Manado. This study contributes in two ways: first, the availability of an integrated web-based transmitter report management system that can be adopted by similar public broadcasting stations; second, the provision of empirical evidence of the system's usability level through standardized testing, which can serve as a reference for the development of similar systems in the future.